Fabrication and characterization of silicon based vertical electrode nanogap biosensor for protein detection - Norbi Hayati, Mohd Noor (Universiti Malaysia Perlis, 2011)
The nanogap biosensor is a new class of device that has attracted attention and great interest among the researchers due to their potential applications in nanotechnology. This nanogap device which are fabricated using standard Complimentary Metal Oxide Semiconductor (CMOS) technology, have the potential to serve as the biomolecular junctions because their size reduces electrode polarization effects regardless of frequency. This junction technology is essentially a biology-to-digital converter system that enables real time conversion of biomolecular dielectric signals into digital information. This nanogap biosensor consists of a heavily doped silicon substrate electrode and poly-silicon electrode vertically separated by a fixed distance of 80 nm silicon oxide spacer. The process flow development in this research consists of detailed parameters and recipes to define the nanogap spacer. Two (2) types of masks are used in the process which are the Electrode Mask and the Aluminum Pad Mask. Both masks are designed by using the AutoCAD software and transferred onto a transparency. The main focus in this research is to create the gap spacer by using Inductive Coupled Plasma – Reactive Ion Etch (ICP- RIE) to etch the poly-silicon layer and buffered hydrofluoric acid (HF) to etch the silicon oxide layer. However, the silicon oxide was not completely etched, so that the remaining will act as the mechanical spacer gap. The final step involved sputtering and patterning aluminum onto contact pads using a standard photolithography technique. This was done to help minimize the variability in contact resistance when the nanogap device was probed. The overall goal of this research is to design, fabricate, characterize, and test the silicon based vertical electrode nanogap biosensor that will be used to detect and identify target proteins in aqueous solution.